PKM Inovasi Sistem Rotasi Tanam Menuju IP400 Sistem Padi-Jagung-Melon-Semangka “PAJAMEKA” - Masluki, Masluki; Mutmainnah, Mutmainnah; Firdamayanti, Erni (MALLOMO: Journal of Community Service, 2023)
Abstract. Community service activities (PKM) with the theme Planting Rotation System Innovation Towards IP400 Rice-Corn-Melon-Watermelon System "PAJAMEKA" in collaboration with the Mujur farmer group, Salujambu Village, Lamasi District, Luwu Regency. The Mujur farmer group has 30 group members with a technically irrigated rice field area of ​​24 ha. PKM activities aim to increase the capacity and welfare of farmers in utilizing rice fields after harvest through a crop rotation system based on corn, melon and watermelon commodities. The activity method is to develop a three-commodity formulation starting with location transects, FGDs, training, counseling, field schools and plot demonstrations. The highest problem for partner farmers is business capital at 30%. The communication, managerial, capital and capability aspects have the lowest value, namely 3.33%, the highest level of participation of partner farmers is in the FGD component at 93.33%. The lowest component was found in demo plot activities at 66.67%. The involvement of partner farmers in FGD activities has a level of correlation with the interest in the problems and solutions that will be offered by the PKM team. The highest farmer capacity indicator is in the active participation aspect at 70%, while the lowest farmer capacity indicator is in the motivation component at 50%. The ability of farmers to express opinions and receive training and counseling materials will have an impact on increasing farmers' capacity and welfare. Abstrak. Kegiatan pengabdian kepada Masyarakat (PKM) dengan tema Inovasi Sistem Rotasi Tanam Menuju IP400 Sistem Padi-Jagung-Melon-Semangka “PAJAMEKA” bekerja sama dengan kelompok tani Mujur Desa Salujambu Kecamatan Lamasi Kabupaten Luwu. Kelompok tani Mujur memiliki anggota kelompok sebanyak 30 orang dengan luas lahan sawah beirigasi teknis sebesar 24 ha. Kegiatan PKM bertujuan untuk meningkatkan kapasitas dan kesejahteraan petani dalam memanfaatkan lahan sawah setelah panen melalui sistem rotasi tanam berbasis komoditi jagung, melon dan semangka. Metode kegiatan dengan mengembangkan formulasi tiga komoditi yang diawali dengan transek lokasi, FGD, pelatihan, penguluhan, sekola lapang dan demo plot. Permasalahan petani mitra tertinggi terdapat pada modal usaha sebesar 30%. Aspek komunikasi, manajerial, modal dan kapabilitas memiliki nilai terendah yaitu 3,33%, tingkat partisipasi kehadiran petani mitra tertinggi terdapat pada komponen FGD sebesar 93,33%. Komponen terendah terdapat pada kegiatan demo plot sebesar 66,67%. Keterlibatan petani mitra dalam kegiatan FGD memiliki tingkat korelasi dengan kepentingan akan permasalahan dan solusi yang akan ditawarkan oleh tim PKM. Indikator kapasitas petani tertinggi terdapat pada aspek partisipasi aktif sebesar 70% sedangkan indikator kapasitas petani terendah terdapat pada komponen motivasi sebesar 50%. Kemampuan petani menyampaikan pendapat dan menerima materi pelatihan dan penyuluhan akan berdampak pada peningkatan kapasitas dan kesejahteraan petani.